Effect of seed moisture, temperature, and packaging on soybean seed longevity and quality - López-Rodríguez, José Israel (2026)
Introduction. Seed quality is a key component for maintaining soybean crop yield; however, it can be affected by seed moisture content, temperature, and packaging management during storage. Objective. To evaluate the effect of temperature, seed moisture content, and packaging factors on the longevity and physiological quality of soybean seeds of the CIGRAS-06 variety. Materials and methods. This work was carried out at the Center for Research in Grains and Seeds (CIGRAS), University of Costa Rica, during 2022 and 2023. Seed lots from Guanacaste and Pérez Zeledón were used. Seeds were conditioned and dried to 6 % and 12 % moisture content and stored for 12 months under cold (6 ¡C) and room temperature (23 ¡C) conditions in three types of packaging (polyethylene bag, polypropylene sack, and vacuum bag). Germination and seed vigor tests were conducted. Results. An interaction among the studied factors was observed, with storage temperature and site of origin being significant. Seeds from Pérez Zeledón stored at 23 ºC showed greater deterioration, whereas cold storage (6 ºC) and lower moisture content (6 %) reduced germination loss, particularly in the Guanacaste seed lot. Environmental conditions at 23 ºC accelerated seed deterioration and decreased seed vigor, as quantified by electrical conductivity. Conclusions. Storage of the CIGRAS-06 soybean variety was favored under conditions of 6 ºC and a seed moisture content of 6 %. The origin of the seed must be considered, as it also influences the response observed in the different treatments.